Quelques légendes montagnaises - anonyme, (Anthropologica, 2022)
Legends are a good means of understanding a people's mind and beliefs. The Canadian Indians have many interesting legends and it seemed that some contained in the Diary of the Catholic mission of Reindeer Lake deserved to be known. Following are two narrations concerning deluge and one on the origin of mosquitoes.